2002
DOI: 10.1099/00221287-148-1-191
|View full text |Cite
|
Sign up to set email alerts
|

Ras1 and Ras2 contribute shared and unique roles in physiology and virulence of Cryptococcus neoformans The GenBank accession number for the RAS2 sequence of C. neoformans H99 is AF294349.

Abstract: The Ras1 signal transduction pathway controls the ability of the pathogenic fungus Cryptococcus neoformans to grow at high temperatures and to mate. A second RAS gene was identified in this organism. RAS2 is expressed at a very low level compared to RAS1, and a ras2 mutation caused no alterations in vegetative growth rate, differentiation or virulence factor expression. The ras2 mutant strain was equally virulent to the wild-type strain in the murine inhalational model of cryptococcosis. Although a ras1 ras2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 33 publications
6
118
0
1
Order By: Relevance
“…The alignment score between the deduced amino acid sequence and the Ras1p gene submitted by Gorfer is 98% (data not shown), and therefore these genes were considered homologous. However, it remains to be seen whether another RAS gene exists in S. commune as in C. neoformans, 32) and homobasidiomycete Suillus bovinus ras1 and ras2. Since the amino acid sequences of the RAS gene have been well conserved in most species, it might be possible to discover other RAS genes in S. commune by degenerate PCR or substitutional techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The alignment score between the deduced amino acid sequence and the Ras1p gene submitted by Gorfer is 98% (data not shown), and therefore these genes were considered homologous. However, it remains to be seen whether another RAS gene exists in S. commune as in C. neoformans, 32) and homobasidiomycete Suillus bovinus ras1 and ras2. Since the amino acid sequences of the RAS gene have been well conserved in most species, it might be possible to discover other RAS genes in S. commune by degenerate PCR or substitutional techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In Cr. neoformans, Ras1 expression is higher than Ras2 and the protein functions mainly overlap (114). Interestingly, in Cr.…”
Section: Monomeric Gtpases Ras and Cdc42mentioning
confidence: 97%
“…The function of Ras proteins encoded by two different genes, Ras1 and Ras2, has been extensively analyzed in S. cerevisiae (108), Cr. neoformans (68,69,114,115,118), and U. maydis (52,64). Several aspects complicate the understanding of the function of Ras proteins, as Ras gene expression is often controlled by nutritional and environmental factors.…”
Section: Monomeric Gtpases Ras and Cdc42mentioning
confidence: 99%
“…C. neoformans also possesses a Ras2 protein. On their own, ras2 mutants display no obvious phenotypes, although an overexpression of RAS2 is able to partially suppress ras1 mutant phenotypes (619). Additional studies have shown that ras1 mutants are viable but are unable to grow at elevated temperatures, show defects in mating and agar adherence, and are avirulent in rabbit models of cryptococcal meningitis (9).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%